The Role of Islamic Ethic Investment in Aceh - Malahayatie Malahayatie; Rahmawati Rahmawati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2022)
Investment has important role in economic development of Aceh.However, many investors tend to violate the work ethics while workingwith the enterpreneurs and local goverment. This study aimed to observe TheRole of Islamic Ethic for Synergy Form and Domestic Investment Contributionamong the Enterpreneurs and Goverment of Aceh. This is a qualitative descriptive study using survey method. The respondents were enterpreneurs andlocal Government of Aceh. The results of this study show that the Islamic ethic has important role in forming work synergy between the enterpreneurs and Aceh Government contributing to the invesments in Aceh.